Enhancement of fingermarks and visualizing DNA. (July 2019) - Kanokwongnuwut, P.; Kirkbride, K.P.; Kobus, H.; Linacre, A.
Highlights: Diamond™ dye (DD) is a non-destructive dye that can visualize touch DNA. Touch DNA can be visualized after fingermark enhancement have been performed. Inhibition of DNA profiling after DD staining and enhancement was examined. DNA profiles were obtained from treated marks except after cyanoacrylate treatment. Abstract: A novel method for detection and visualization of latent DNA using Diamond™ Nucleic Acid Dye (DD) staining has been developed. Applying DD to an object has the real potential to visualize DNA on a substrate from which a DNA profile can be generated, but it is important to determine whether this staining will adversely affect other forensic investigational techniques and vice versa. The aim of this study was to examine the interactions between staining a fingermark to detect DNA and then generate a DNA profile in combination with several standard latent fingermark enhancement methods. Six common fingerprint enhancements processes were chosen; (1) black powder, (2) black magnetic powder, (3) red magnetic powder, (4) white powder, (5) aluminum powder and (6) cyanoacrylate fuming. For all six methods, mark enhancement was carried out before DD staining and vice versa. DD is effective in detection of DNA in the presence of both aluminum and white finger mark powders and DD does not compromise the subsequent detection of ridge patterns if DD is applied first. Whilst magnetic powders could be used to successfully enhance latent fingermarks even after DD had been applied to them, latent DNA could not be observed in the marks irrespective of whether magnetic powder was applied before or after DD treatment. Magnetic powders did not adversely affect the profiling of DNA present in the marks. The application of DD to fingermarks did not adversely affect the enhancement of fingermarks using cyanoacrylate fuming. Whilst fluorescent particles resembling cells stained with DD were observed in marks either post-treated or pre-treated with cyanoacrylate vapor, DNA amplification and profiling was not successful. While it may be important in particular investigations to collect DNA profiles from latent fingermarks with continuous ridges and clear minutiae, the main utility of the technique described here would be in relation to investigations where enhancement has resulted in only partial or smudged marks. The results presented here indicate that if it is desirable to visualize latent DNA on an object but it is also planned to treat the object with cyanoacrylate vapor or magnetic powders then it is important to apply DD first, record the location of DNA and then apply the mark enhancement technique. For aluminum and white powder mark treatments such precautions are not important.